MANAJEMEN PENDIDIKAN POLITIK MASYARAKAT PERBATASAN DI KALIMANTAN BARAT - Mujiono Mujiono (CV. ADIBA AISHA AMIRA, 2022)
The aim of this case study for build nationality commitment through political education, and the results that their cultural background border community profile, and the contains of the connections across the border communities that can not be avoided. the process of life together in the territory of each country. The relationship clumps ethnic tribes share a common culture are interrelated. Political education to revive awareness through the study of national and state political education that emphasizes obligation of citizens to establish intensive communication with the government's public relations border with instilling a sense of bigotry tot the nation and the state. Border communities need balance the needs living standards through economic infrastructure, and needs improving the well-being by providing facilities that can trigger a more dynamic economic activity, in order to participation formaintain the territorial integrity through national unity political, economic, social and cultur approach.